Phosphate binding therapy in dialysis patients: focus on lanthanum carbonate - Ismail A Mohammed; Alastair J Hutchison (Dove Medical Press, 2008)
Ismail A Mohammed, Alastair J HutchisonManchester Institute of Nephrology and Transplantation, Manchester Royal Infirmary, Oxford Road, Manchester, UKAbstract: Hyperphosphatemia is an inevitable consequence of end stage chronic kidney disease and is present in the majority of dialysis patients. Recent observational data has associated hyperphosphatemia with increased cardiovascular mortality among dialysis patients. Dietary restriction of phosphate and current dialysis prescription practices are not enough to maintain serum phosphate levels within the recommended range so that the majority of dialysis patients require oral phosphate binders. Unfortunately, conventional phosphate binders are not reliably effective and are associated with a range of limitations and side effects. Aluminium-containing agents are highly efficient but no longer widely used because of well established and proven toxicity. Calcium based salts are inexpensive, effective and most widely used but there is now concern about their association with hypercalcemia and vascular calcification. Sevelamer hydrochloride is associated with fewer adverse effects, but a large pill burden and high cost are limiting factors to its wider use. In addition, the efficacy of sevelamer as a monotherapy in lowering phosphate to target levels in severe hyperphosphatemia remains debatable. Lanthanum carbonate is a promising new non-aluminium, calcium-free phosphate binder. Preclinical and clinical studies have demonstrated a good safety profile, and it appears well tolerated and effective in reducing phosphate levels in dialysis patients. Its identified adverse events are apparently mild to moderate in severity and mostly GI related. It appears to be effective as a monotherapy, with a reduced pill burden, but like sevelamer, it is significantly more expensive than calcium-based binders. Data on its safety profile over 6 years of treatment are now available.Keywords: hyperphosphatemia, lanthanum carbonate, dialysis, phosphate binding